Breeding Practices Followed in Dairy Animals by Farmers of Kheda and Panchmahal Districts of Middle Gujarat - Divekar, BS; Trivedi, MM (Indian Journal of Veterinary Sciences and Biotechnology, 2015)
This study was undertaken in Kheda and Panchmahal districts of middle Gujarat to assess existing breeding practices followed by the dairy farmers. The study was conducted in randomly selected four talukas each from Kheda and Panchmahal districts. From each taluka five villages and from each village five respondents were randomly selected. Thus, total 200 respondents were included in the study. Data revealed that majority of the respondents (49.00 %) were keeping buffaloes only. Mucus discharge alongwith bellowing and frequent urination were the predominant heat symptoms as perceived by majority of the respondents. Majority of the respondents (92.50 %) were taking their anestrous animals for treatment. Overall, majority (82.50 %) of the respondents were using artificial insemination for breeding their animals. Further majority of the dairy farmers (64.50 %) were inseminating their dairy animals between 12 and 24 hrs after heat detection. Moreover, almost all dairy farmers (97.00 %) were taking their animals for pregnancy diagnosis. Breeding records were maintained by more than three fourth (77.00 %) of the respondents. Almost all (99.00 %) dairy farmers disposed the placental membranes by burial method. The findings revealed higher level of awareness for breeding practices among dairy farmers of middle Gujarat.